Variability of food stores of Tetragonisca fiebrigi (Schwarz) (Hymenoptera: Apidae: Meliponini) from the Argentine Chaco based on pollen analysis - Vossler, Favio Gerardo (2014)
Honey and pollen mass samples of Tetragonisca fiebrigi (Schwarz) from the same and different nests, seasons, and forest types from the Argentine Chaco region were palynologically analyzed and multivariate techniques were applied. The samples from each forest type (Palosantal and Quebrachal) were grouped separately by Cluster Analysis but the phenological records detected that grouping was determined by the season when samples were taken. Honeys and pollen masses were grouped together or fairly closed for all nests due to similar abundance of the different pollen types. Furthermore, honeys were not clustered together with other honeys but with pollen masses. It can be assumed that both nectar and pollen were gathered from the same plant species, supporting the hypothesis that the Dry Chaco melittophilous vegetation is dominated by plants providers of both pollen and nectar, but not exclusively or predominately of one of them. Results of Principal Component Analysis revealed that the foraging behavior of T. fiebrigi was governed by random factors such as local differences of flower availability but not by preferences for some plant families. This idea can also be extended to other species of this genus as they concentrated their foraging on different families according to the local vegetation availability in the studied sites.